Application of Constitutive Friction Laws to Glacier Seismicity. Issue 21 (26th October 2020) - Zoet, L. K.; Ikari, M. J.; Alley, R. B.; Marone, C.; Anandakrishnan, S.; Carpenter, B. M.; Scuderi, M. M.
Abstract: While analysis of glacial seismicity continues to be a widely used method for interpreting glacial processes, the underlying mechanics controlling glacial stick‐slip seismicity remain speculative. Here, we report on laboratory shear experiments of debris‐laden ice slid over a bedrock asperity under carefully controlled conditions. By modifying the elastic loading stiffness, we generated the first laboratory icequakes. Our work represents the first comprehensive lab observations of unstable ice‐slip events and replicates several seismological field observations of glacier slip, such as slip velocity, stress drop, and the relationship between stress drop and recurrence interval. We also observe that stick‐slips initiate above a critical driving velocity and that stress drop magnitude decreases with further increases in velocity, consistent with friction theory and rock‐on‐rock friction laboratory experiments. Our results demonstrate that glacier slip behavior can be accurately predicted by the constitutive rate‐and‐state friction laws that were developed for rock friction. Plain Language Summary: Glacier beds and tectonic faults may at first appear to be quite different, but they share important characteristics. In both cases, motion may be smooth (aseismic creep) or earthquake‐producing "stick‐slip." A powerful physical constitutive relationship called rate‐and‐state friction has been developed to understand earthquakes and smooth slip on tectonic faults. Laboratory experiments reported here simulate glacier‐bed motion by sliding debris‐bearing ice over a rock plate under conditions that are typical for glacier beds. They produce the first laboratory icequakes. Transitions between steady and stick‐slip motions are generated by controlling shearing velocity and other conditions, as predicted by rate‐and‐state friction theory. Future studies can thus apply this physical framework to glacier slip, helping to understand ice motion and its potential to accelerate sea level rise in a warming world. Furthermore, because motion at the glacier bed is often much easier to study than tectonic faults, additional observations of glaciers may provide useful insights into earthquake behavior. Key Points: The first laboratory "icequakes" were generated and slip stability was predicted well by rate‐and‐state friction Laboratory icequake attributes such as peak slip velocity, stress drop and healing agree well with other laboratory and field observations The laboratory icequake events suggest that debris‐bed contacts dominate the sudden slip mechanics